Apoptotic and antihepatofibrotic effect of honokiol via activation of GSK3β and suppression of Wnt/β‐catenin pathway in hepatic stellate cells. (10th August 2020) - Lee, Il Ho; Im, Eunji; Lee, Hyo‐Jung; Sim, Deok Yong; Lee, Jae Hee; Jung, Ji Hoon; Park, Ji Eon; Shim, Bum Sang; Kim, Sung‐Hoon
Abstract : Though honokiol, derived from the Magnolia tree, was known to suppress renal fibrosis, pulmonary fibrosis, non‐alcoholic steatoheptitis, inflammation and cancers, the underlying antifibrotic mechanisms of honokiol are not fully understood in hepatic stellate cells until now. Thus, in the present study, inhibitory mechanism of honokiol on liver fibrosis was elucidated mainly in hepatic stellate cells (HSCs) by 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) assay, cell cycle analysis and western‐blotting. Honokiol exerted cytotoxicity in LX‐2, HSC‐T6 and Hep‐G2 cells. Honokiol increased sub G1 population and activated caspase 3 and cleaved poly (ADP‐ribose) polymerase (PARP) in HSCs. Moreover, honokiol attenuated the expression of alpha smooth muscle actin (α‐SMA), transforming growth factor beta 1 (TGF‐β1), phospho‐Smad3, phospho‐AKT, cyclin D1, c‐Myc, Wnt3a, β‐catenin, and activated phosphorylation of glycogen synthase kinase 3 beta (GSK3β) in HSCs. Conversely, GSK3β inhibitor SB216763 reversed the effect of honokiol on PARP, α‐SMA, phospho‐GSK3β, β‐catenin and sub G1 population in LX‐2 cells. Overall, honokiol exerts apoptotic and antifibrotic effects via activation of GSK3β and inhibition of Wnt3a/β‐catenin signalling pathway.